Effects of propeller thrust trimming on tailless unmanned aerial vehicle performance. (April 2016) - Wang, Gang; Yu, Hu; Bi-feng, Song
Flight performance and longitudinal static stability are two contradictory requirements for aircraft. This is especially true for a tailless configuration, whose flight performance is traded for static stability. A new tailless gull wing configuration with propeller thrust trimming is proposed in this paper. It is expected that the propeller thrust can help to provide a nose-up pitching moment and improve the flight performance. In the present configuration, a cambered airfoil is used to increase the lift-to-drag ratio as well as the maximum lift coefficient. Two approaches are adopted to obtain the nose-up pitching moment. Firstly, the thrust line is shifted below the center of gravity to make a positive contribution to the pitching moment. Secondly, the thrust vectoring is employed to trim longitudinally instead of elevon deflection. The wind-tunnel data indicate that the lift-to-drag ratio and maximum lift coefficient increase notably with the help of propeller thrust trimming. To determine the performance benefits of the gull wing with propeller thrust trimming, a conceptual design environment of the electric-powered unmanned aerial vehicle is developed by integrating the modules of the conceptual parameters, aerodynamics, stability, propulsion, weight, performance, as well as optimization. The optimization results suggest that, compared with the two other conventional tailless configurations, the gull wing with propeller thrust trimming results in 20 and 34% endurance increase. Flight tests of a 2.5 kg built aircraft demonstrate the aerodynamic feasibility of the gull wing with propeller thrust trimming concept.